UPAYA MEMPERTAHANKAN LOYALITAS NASABAH PRODUK DEPOSITO DI BANK MUAMALAT INDONESIA CABANG PANGKALPINANG - Alzikri, Bapaqih Alzikri (Faculty of Economics Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The background of the selection of this theme is because of the data obtained from the Bank of Muamalat Indonesia, Pangkalpinang Branch on the collection of third party funds (DP3) for the performance of deposit products indicating an increase in funds collected which shows the increasing number of people who are interested in depositing funds through bank deposit products. muamalat, here the question arises in the minds of researchers how to maintain customer loyalty deposit products at the bank Muamalat Indonesia branch of Pangkalpinang. The results of the study through interviews with leaders, head funding, and marketing funding concluded that efforts to maintain customer loyalty for deposit products at Bank Muamalat Indonesia at Pangkalpinang Branch were to give special attention, provide the best service, create mutually beneficial relationships, carry out ongoing follow-up, offer attractive programs for maintain customer loyalty, and give appreciation to loyal customers. While the obstacles faced in the effort to maintain customer loyalty deposit products at the bank Muamalat pangkalpinang branch from the results of interviews with head funding and marketing funding of Muamalat Indonesia Bank, Pangkalpinang Branch are competition between banks, economic conditions, different levels of customer satisfaction, limitations funds for customer maintenance, distance between office and customer, sometimes the bank does not have an active customer telephone number, does not know the customer's residence, and customer dishonesty.